Resting Metabolic Rate Does Not Change in Response to Different Types of Training in Subjects with Type 2 Diabetes - Karstoft, Kristian; Brinkløv, Cecilie Fau; Thorsen, Ida Kær; Nielsen, Jens Steen; Ried-Larsen, Mathias (Frontiers in Endocrinology, 2017)
Background and objectives Ambiguous results have been reported regarding the effects of training on resting metabolic rate (RMR), and the importance of training type and intensity is unclear. Moreover, studies in subjects with type 2 diabetes (T2D) are sparse. In this study, we evaluated the effects of interval- and continuous training on RMR in subjects with T2D. Furthermore, we explored the determinants for training-induced alterations in RMR. Methods Data from two studies, both including T2D subjects, were encompassed in this manuscript. Study 1 was a randomized, cross-over study where subjects (n=14) completed three, 2-week interventions (control [CON], continuous walking training [CWT], interval-walking training [IWT]) separated by washout periods. Training included 10 supervised treadmill sessions, 60 min/session. CWT was performed at moderate walking speed (aiming for 73% of walking peak oxygen uptake [VO2peak]), while IWT was performed as alternating 3-minute repetitions at slow (54% VO2peak) and fast (89% VO2peak) walking speed. Study 2 was a single-arm training intervention study where subjects (n=23) were prescribed 12 weeks of free-living IWT (at least 3 sessions/week, 30 min/session). Before and after interventions, RMR, physical fitness, body composition and glycemic control parameters were assessed. Results No overall intervention-induced changes in RMR were seen across the studies, but considerable inter-individual differences in RMR changes were seen in Study 2. At baseline, total body mass, fat free mass and fat mass were all associated with RMR. Changes in RMR were associated with changes in total body mass and fat mass and subjects who decreased body mass and fat mass also decreased their RMR. No associations were seen between changes in physical fitness, glycemic control or fat free mass and changes in RMR. Conclusions Neither short-term continuous or interval-type training, nor longer-term interval training affects RMR in subjects with T2D when no overall changes in body composition are seen. If training occurs concomitant with a reduction in fat mass, however, RMR is decreased.